A Effect of compost with banana peel and Moringa leaf powders on crop residue and seed yield of green gram (Vigna radiata L. Wilczek): Use of banana peel and Moringa leaf powders in green gram cultivation. - Fernando , W. K. Madhuri B. Fernando; Seran, Thayamini (Journal of Agricultural Sciences (Belgrade), 2023)
The experiment was carried out to study the effect of compost with powdered banana peel and Moringa leaf powders on seed yield and crop residue of green gram (Vigna radiata L. Wilczek). It was laid out in a Complete Randomized Design with eight replicates with the following treatments: T1 - Control (100 g Compost alone), T2 - 100 g Compost + 9 g banana peel, T3 - 100 g Compost + 6 g banana peel + 3 g Moringa leaf, T4 - 100 g Compost + 4.5 g banana peel + 4.5 g Moringa leaf, T5 - 100 g Compost + 3 g banana peel + 6 g Moringa leaf and T6 - 100 g Compost + 9 g Moringa leaf powder per polybag (0.07 m2). The results showed that different ratios of banana peel and Moringa leaf powders had significant influences on some tested yield parameters of green gram over the control. Application of compost with 4.5 g banana peel and 4.5 g Moringa leaf powders (T4) had remarkable variations on the number of pods per plant, pod weight per plant, seed weight per plant, pod yield and seed yield than the other treatments. And there were insignificant differences in pod length, number of seeds per pod, pod weight, seed weight per pod, 100 seed weight, dry weight of stem, dry weight of leaves and weight of crop residue per plant among the treatments even though T4 increased the pod length, number of seeds per pod, pod weight, seed weight per pod, 100 seed weight, dry weight of stem, dry weight of leaves and weight of crop residue per plant than the control treatment. At the harvest, T4 treatment had the highest value (1,587.1 kg/ha) of seed yield, and T1 treatment gave the lowest value (906.1 kg/ha). Application of compost with banana peel and Moringa leaf powders improved crop residue and seed yield of green gram in sandy regosol compared to the control treatment (compost alone). The present study suggests that application of 100 g (equivalent to 14.3 t/ha) compost with 9 g (equivalent to 1.3 t/ha) of banana peel and Moringa leaf powders at 1:1 (w/w) ratio would give optimum seed yield of green gram in sandy regosol. The combined use of locally available banana peel and Moringa leaf powders is cost-effective for increasing the seed yield of green gram with less environment effect.
Keywords: banana peel, compost, crop residue, green gram, Moringa leaf, seed yield